Short-term effects of ambient particulates and gaseous pollutants on the incidence of transient ischaemic attack and minor stroke: a case-crossover study - Bedada Getahun; Smith Craig J; Tyrrell Pippa J; Hirst Adrian A; Agius Raymond (BMC, 2012)
Abstract Background While several studies have investigated the effects of short-term air pollution on cardiovascular disease, less is known about its effects on cerebrovascular disease, including stroke and transient ischaemic attack (TIA). The aim of the study was to assess the effects of short-term variation in air pollutants on the onset of TIA and minor stroke. Methods We performed secondary analyses of data collected prospectively in the North West of England in a multi-centre study (NORTHSTAR) of patients with recent TIA or minor stroke. A case - crossover study was conducted to determine the association between occurrence of TIA and the concentration of ambient PM10 or gaseous pollutants. Results A total of 709 cases were recruited from the Manchester (n = 335) and Liverpool (n = 374) areas. Data for the Manchester cohort showed an association between ambient nitric oxide (NO) and risk of occurrence of TIA and minor stroke with a lag of 3 days (odds ratio 1.06, 95% CI: 1.01 - 1.11), whereas negative association was found for the patients from Liverpool. Effects of similar magnitude, although not statistically significant, were generally observed with other pollutants. In a two pollutant model the effect of NO remained stronger and statistically significant when analysed in combination with CO or SO2, but was marginal in combination with NO2 or ozone and non-significant with PM10. There was evidence of effect modification by age, gender and season. Conclusions Our data suggest an association between NO and occurrence of TIA and minor stroke in Greater Manchester.